Confirmatory Factor Analysis of the Perceived Stress Scale‐4 in a Community Sample. (4th July 2014) - Ingram, Paul B.; Clarke, Erik; Lichtenberg, James W.
Abstract: Although the Perceived Stress Scale (PSS) is among the most widely used measures of perceived stress, it has only recently begun to be tested in independent psychometric validation studies, and the four‐item version of the PSS (PSS‐4) (the briefest version of this measure) has never undergone testing to examine and confirm the originally proposed structure. To address this paucity of research, the present study (a) tested the structure of the PSS‐4 in the first confirmatory factor analysis of the instrument and (b) tested for item‐level gender differences in the PSS that have been demonstrated in other versions of this scale. Results indicated that the PSS four‐item measure does not fit its proposed model. Additionally, score differences were observed for one item across genders. Copyright © 2014 John Wiley & Sons, Ltd.